$3\,\left[ {{{\sin }^4}\,\left( {\frac{{3\pi }}{2} - \alpha } \right) + {{\sin }^4}\,(3\pi + \alpha )} \right]$ $ - 2\,\left[ {{{\sin }^6}\,\left( {\frac{\pi }{2} + \alpha } \right) + {{\sin }^6}(5\pi - \alpha )} \right] = $
$0$
$1$
$3$
$\sin \,4\alpha + \sin \,6\alpha $
$\frac{{\cos A}}{{1 - \sin A}} = $
$\sqrt 2 + \sqrt 3 + \sqrt 4 + \sqrt 6 = $
यदि $\sin \theta + \sin 2\theta + \sin 3\theta = \sin \alpha $ तथा $\cos \theta + \cos 2\theta + \cos 3\theta = \cos \alpha $, तब $\theta$ का मान होगा
यदि $\sin \alpha = \frac{{ - 3}}{5},$ जहाँ $\pi < \alpha < \frac{{3\pi }}{2},$ तो $\cos \frac{1}{2}\alpha = $
यदि $\tan \alpha = \frac{1}{7},\;\tan \beta = \frac{1}{3},$ तब $\cos 2\alpha = $